ESC Working Group on Coronary Pathophysiology and Microcirculation position paper on 'coronary microvascular dysfunction in cardiovascular disease'. Issue 4 (8th February 2020) - Padro, Teresa; Manfrini, Olivia; Bugiardini, Raffaele; Canty, John; Cenko, Edina; De Luca, Giuseppe; Duncker, Dirk J; Eringa, Etto C; Koller, Akos; Tousoulis, Dimitris; Trifunovic, Danijela; Vavlukis, Marija; et al.
: Although myocardial ischaemia usually manifests as a consequence of atherosclerosis-dependent obstructive epicardial coronary artery disease, a significant percentage of patients suffer ischaemic events in the absence of epicardial coronary artery obstruction. Experimental and clinical evidence highlight the abnormalities of the coronary microcirculation as a main cause of myocardial ischaemia in patients with 'normal or near normal' coronary arteries on angiography. Coronary microvascular disturbances have been associated with early stages of atherosclerosis even prior to any angiographic evidence of epicardial coronary stenosis, as well as to other cardiac pathologies such as myocardial hypertrophy and heart failure. The main objectives of the manuscript are (i) to provide updated evidence in our current understanding of the pathophysiological consequences of microvascular dysfunction in the heart; (ii) to report on the current knowledge on the relevance of cardiovascular risk factors and comorbid conditions for microcirculatory dysfunction; and (iii) to evidence the relevance of the clinical consequences of microvascular dysfunction. Highlighting the clinical importance of coronary microvascular dysfunction will open the field for research and the development of novel strategies for intervention will encourage early detection of subclinical disease and will help in the stratification of cardiovascular risk in agreement with the new concept of precision medicine.